Vocational Training Needs of Rural Youth in Agriculture for Self-employment in Udham Singh Nagar of Uttarakhand - Debashis Dash and B. Kumar (Indian Journal of Extension Education, 2023)
Making rural youth employable is a big challenge to the menace of unemployment and underemployment.Government is putting efforts towards conducting skill based trainings as trained and productively engagedyouth can bring miracles for the nation. The present study was carried out to find out the vocational trainingneeds of rural youth in agriculture related areas. Qualitative and quantitative investigation was carried outin Udham Singh Nagar district of Uttarakhand using analytical research design. Youth (n=120) were selectedfrom three villages representing agricultural progressiveness in decreasing order through disproportionatestratified random sampling. Pre-tested interview schedule was used for data collection. Maximum trainingneed in major agricultural vocations was found to be in fruit and vegetable production (2.050) followed bycattle farming (2.008), Mushroom Production (1.975) Floriculture (Protected Cultivation) (1.933), Poultry(1.658), Vermi-culture (1.616), Fishery (1.541), Bee keeping (1.508), Rabbit farming (1.450) and Sericulture(1.425). Training needs in subareas of major vocations were also calculated. Village was the most favourablearea in receiving training for about two months in Rabi season at the morning time. Scientists anddemonstrators were preferred the most along with regular trainings and fortnight demonstrations. Amongpsychological characteristics, achievement motivation (r = 0.188, tcal=2.079) had a significant positiverelationship with vocational training needs of rural youth whereas innovativeness, leadership ability, riskpreference and occupational Aspiration had non-significant but positive relationships with vocational trainingneeds of rural youth in agriculture related areas.